Fundamentals of international aviation law and policy - Scott, Benjamyn I.; Trimarchi, Andrea (Abingdon, Oxon [UK] ; New York, NY : Routledge, 2024)
"Fundamentals of International Aviation Law and Policy offers students a systematic, tailored and dynamic approach to understanding the legal scenario concerning international civil aviation. The book covers the major areas of international aviation law and provides an introduction to the multifaceted international regulation of aviation activities in the sphere of public and private law. The book is designed to provide the reader with the fundamental notions concerning international aviation law. It adopts an interactive approach, which aims at engaging the reader by way of using learning tools. The main areas of public and private aviation law are dealt with from a regulatory and practical perspective, and include detailed analyses of existing and applicable legislations, as well as landmark court cases and decisions. Each chapter is tailored to confer to readers a thorough knowledge of the international and, if any, the European applicable legislation. Delivery of these aims is attained through a clear and balanced use of didactic instruments and immediate information. New chapters cover aircraft financing and advanced air mobility, giving this second edition of Fundamentals of International Aviation Law and Policy even greater coverage and depth. The book is intended for a varied audience of students and professionals involved in the aviation world, without requiring the possession of specific legal knowledge or background. It also constitutes a useful reference material for those who are familiar with legal terminology and aviation specifics"--
Foundations of Aviation Law -- Early Development in Air Law -- Convention on International Civil Aviation -- International Civil Aviation Organization -- International Air Transport -- Criminal Aviation Law -- Contractual Liability -- Third Party Liability and Damage on the Surface -- Aviation Insurance -- Aviation Competition Law -- Regulation of Environment in Aviation -- Suborbital Transportation and the Link to Space Law.
Keywords: Aeronautics -- Law and legislation; TRANSPORTATION / Aviation / General; LAW / Air & Space; TECHNOLOGY / Aeronautics & Astronautics